Durability control of UV radiation in glass fiber reinforced polymer (GFRP) - A review - Syamsir A.; Ishak Z.A.M.; Yusof Z.M.; Salwi N.; Nadhirah A. (American Institute of Physics Inc., 2023)
Glass Fiber Reinforced Polymer (GFRP) was commonly used as outer layer, and it may expose to the ultraviolet exposure and prone to UV radiation. UV radiation will lead to degradation of the GFRP itself and it will reduce the quality and function of GFRP. This paper is a review of past studies on UV Radiation of Glass Fiber Reinforced Polymer (GFRP) in transmission line tower. A study on UV radiation toward coupling steel laminates of GFRP pultruded show the load carry the capacity of the joint was found to be increase, it was due to polymerization of the adhesives. While, a study of UV radiation on GFRP show during the aging process GFRP show signs of plasticization and after 6 months the tensile strength of GFRP show substantial descending pattern and the tensile modulus were found less affected compared to tensile strength. Glass Fiber Reinforced Polymer (GFRP) has a good potential as a material to resist UV radiation. 2018 Author(s).